Marketability of hibah amanah: a case study at Tabung Haji Johor Bahru / Asma Nurul 'Aqilah Mahpuz - Mahpuz, Asma Nurul 'Aqilah (Academy of Contemporary Islamic Studies, 2018)
2010 had leaves a scratch for Malaysia with 1073 unsolved cases related to the mal cases (including inheritance cases) and it keep increasing in number year by year (Annual report of Federal Territory Syariah Court, 2010).The increasing number of frozen assets had call for a need to introduce an alternative instrument in distributing Muslim's wealth. Tabung Haji as one of the financial institution had provides an initiative as a backdoor in distributing their depositors saving. The purpose of this research is to analyse the level of relationship between knowledge of depositors and contribution of depositor on the hibah amanah. This research also aims to construct relationship between the approaches used by Tabung Haji in promoting the product with the participation of depositor in hibah amanah. The main objective is to appraise the marketability of hibah amanah Tabung Haji. However, the research revealed that marketability of hibah amanah had an intermediate low level. In term of medium of approach used by Tabung Haji foresee the web as an effective approach to gather information. Another effective approach towards promoting the hibah amanah is through Tabung Haji branch. Last but not least, there are few recommendations from these findings in enhancing the participation of the depositor and approach used by Tabung Haji. The recommendations were divided into two types which are long term and short term and future study was included at the end of the research.